Health impact of the Tajogaite volcano eruption in La Palma population (ISVOLCAN study): rationale, design, and preliminary results from the first 1002 participants - María Cristo Rodríguez-Pérez; Manuel Enrique Fuentes Ferrer; Luis D. Boada; Ana Delia Afonso Pérez; María Carmen Daranas Aguilar; Jose Francisco Ferraz Jerónimo; Ignacio García Talavera; Luis Vizcaíno Gangotena; Arturo Hardisson de la Torre; Katherine Simbaña-Rivera; Antonio Cabrera de León (BMC, 2024)
Abstract Background The eruption of the Tajogaite volcano began on the island of La Palma on September 19, 2021, lasting for 85 days. This study aims to present the design and methodology of the ISVOLCAN (Health Impact on the Population of La Palma due to the Volcanic Eruption) cohort, as well as the preliminary findings from the first 1002 enrolled participants. Methods A prospective cohort study was conducted with random selection of adult participants from the general population, with an estimated sample size of 2600 individuals. The results of the first 857 participants are presented, along with a group of 145 voluntary participants who served as interveners during the eruption. Data on epidemiology and volcano exposure were collected, and participants underwent physical examinations, including anthropometry, blood pressure measurement, spirometry, and venous blood extraction for toxicological assessment. Results In the general population (n = 857), descriptive analysis revealed that the participants were mostly middle-aged individuals (50.8 ± 16.4), with a predominance of females. Before the eruption, the participants resided at a median distance of 6.7 km from the volcano in the Western region and 10.9 km in the Eastern region. Approximately 15.4% of the sample required evacuation, whose 34.8% returning to their homes on average after 3 months. A significant number of participants reported engaging in daily tasks involving cleaning of volcanic ash both indoors and outdoors. The most reported acute symptoms included ocular irritation, insomnia, mood disorders (anxiety-depression), and respiratory symptoms. Multivariate analysis results show that participants in the western region had a higher likelihood of lower respiratory tract symptoms (OR 1.99; 95% CI:1.33-2.99), depression and anxiety (OR 1.95; 95% CI:1.30-2.93), and insomnia (OR 2.03; 95% CI:1.33-3.09), compared to those in the eastern region. Conclusion The ongoing follow-up of the ISVOLCAN cohort will provide valuable insights into the short, medium, and long-term health impact related to the material emitted during the Tajogaite eruption, based on the level of exposure suffered by the affected population.